Construction and verification of pressure response model for series dual-chamber brake valve in commercial vehicles. Issue 1 (11th June 2022) - Xu, Jun; Yin, Jialiang; Feng, Lan; Li, Gangyan
Abstract: As a key component in pneumatic braking systems, the series dual-chamber brake valve has an important impact on the braking response and braking distance of commercial vehicles. According to its working mechanism, considered with the influence of brake pipeline, this paper presents a simulation model obtaining the valve's dynamic characteristics accurately. A theoretical model for the valve integrated with throttle orifice and gas volume was developed. On this basis, simulation model for the series dual-chamber brake valve was developed and analyzed. A test bench was built, and validity of the model was verified by comparing the simulation results with the experimental ones. The results have shown that maximum value of the root mean square deviation of each pressure measurement point is 0.05 × 10 5 Pa and the correlation coefficient is 0.98. Owing to its effectiveness and accuracy, the response model can be applied in performance analysis, structural design and optimization for the series dual-chamber brake valve in commercial vehicles.